Factors of Deterioration in Building and the Principles of Repair - Mydin, Md Azree Othuman; Ramli, Mahyuddin; Awang, Hanizam (Eftimie Murgu University of Resita, 2012)
Anybody who has owned property recognized that buildings are frequently subject to numerous forms of building defect, regularly in the form of dampness, wall cracks or even a water penetration to the building. Even as the cause of the building defect may be instantly noticeable in several cases, in others the cause is not so understandable. Likewise, there may be an apparent root of a defect, but this may not be the whole story, and the root of the problem may in fact lie elsewhere. An exact identification of a building defect necessitates knowledge and familiarity with the design and construction of a building combined with an indulgent of methods of scientific exploration. An accurate cause of a building defect and the form of its appearance must be understood prior to a sensible remedy can be applied. This paper will discuss on the important factors that affecting the deterioration in building and some principles of repair.